And how enjoyable? Converting a user experience evaluation questionnaire into a voice conversation - Díaz Oreiro, Ignacio (2023)
Voice interfaces have gained popularity, driven by the proliferation of intelligent assistants and the development of natural language processing. Given their progress, they could be used to implement self-reported instruments such as standardized user experience (UX) evaluation questionnaires, particularly in the response capture mechanism. This novel use of voice interfaces wouldmake sense if the evaluations using the voice mechanism did not differ significantly from the evaluations carried out with the traditionalwritten questionnaire. In addition, given different possible implementations of the voice mechanism, it must be analyzed whether the user experience is affected by the format of the instrument used. This paper compares two implementations of the User Experience Questionnaire in which the capture mechanism is implemented by voice. Results show that in both implementations the evaluations retain their validity, and that the use of conversational patterns improves the user experience and increases the quality of the answers, which present fewer inconsistencies.